Synthesis method of 9, 9-di-n-octylfluorene copolymer

The preparation of 9,9-di-octylfluorene copolymer is solved by catalytic reaction of anicyclic carbene palladium complex, and the problem of long synthesis steps of existing organic hole transport layer materials and high toxicity of phosphine ligands is achieved, and the preparation of perovskite solar cell hole transport layer materials with high efficiency catalytic and high efficiency is achieved.

CN119613682APending Publication Date: 2025-03-14CHAIN WALKING NEW MATERIAL TECHNOLOGY (GUANGZHOU) CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411901834.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The commonly used organic hole transport layer material synthesis steps in existing perovskite solar cells are long and expensive, and the phosphine ligand catalysts are highly toxic and harsh.

Method used

The 9,9-di-octylfluorene copolymer was prepared by catalyzed with azocyclic carbene palladium complex. The reaction of 9,9-dioctylfluorene-2,7-bis(boric acid phenarol ester) and 2,5-dichloropyridine under the action of the azocyclic carbene palladium complex and an organic base was obtained to obtain the 9,9-di-octylfluorene copolymer.

Benefits of technology

High-efficiency catalysis was achieved, and a 9,9-di-n-octyl fluorene copolymer with a narrow distribution of high molecular weight was obtained, which overcomes the problems of high toxicity of the phosphine ligand catalyst, and is used to prepare the hole transport layer of perovskite solar cells, improving the efficiency of the solar cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119613682A_ABST
    Figure CN119613682A_ABST
Patent Text Reader

Abstract

The invention discloses a synthesis method of a 9, 9-di-n-octylfluorene copolymer, which comprises the following steps: under the action of an N-heterocyclic carbene palladium complex and organic alkali, reacting 9, 9-dioctylfluorene-2, 7-bis (boronic acid pinacol ester) with 2, 5-dichloropyridine to obtain the 9, 9-di-n-octylfluorene copolymer, and reacting the 9, 9-di-n-octylfluorene copolymer with the boronic acid pinacol ester to obtain the 9, 9-di-n-octylfluorene copolymer. The structure of the N-heterocyclic carbene palladium complex is as shown in a formula (I): # imgabs0 # formula (I); the 9, 9-di-n-octylfluorene copolymer is prepared through catalysis of the N-heterocyclic carbene palladium complex, the 9, 9-di-n-octylfluorene copolymer has the advantage of being high in catalysis efficiency, the 9, 9-di-n-octylfluorene copolymer with high molecular weight and narrow distribution can be obtained, and the problems that a phosphine ligand catalyst is large in toxicity and the like are solved; and the application of the 9, 9-di-n-octylfluorene copolymer in preparation of a hole transport layer of a perovskite solar cell is developed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of organic photoelectric polymer materials, and in particular relates to a method for synthesizing a 9,9-di-n-octylfluorene copolymer. Background Art

[0002] Perovskite solar cells are a type of solar cell that has emerged in recent years and has great development prospects. They have the advantages of high photoelectric conversion efficiency, simple production, and low cost. Photoelectric conversion efficiency is one of the important performance indicators for measuring the quality of perovskite solar cells. At present, there are two main technical means to improve the photoelectric conversion efficiency of perovskite solar cells. One is to optimize the structure or adjust the morphology of each layer of the perovskite solar cell to optimize the interface performance; the other is to change the material composition of the perovskite solar cell and develop hole transport layer, perovskite absorption layer or electron transport layer materials with better performance.

[0003] The hole transport layer is an important component of perovskite solar cells and plays a key role in carrier extraction and transport and inhibiting carrier recombination. Commonly used hole transport layer materials include nickel oxide, cuprous thiocyanate, poly [bis (4-phenyl) (2,4,6-trimethylphenyl) amine] and poly (3,4-ethylenedioxythiophene) and other organic or inorganic materials, but organic hole transport layer materials such as poly [bis (4-phenyl) (2,4,6-trimethylphenyl) amine] and poly (3,4-ethylenedioxythiophene) have disadvantages such as long synthesis steps and high price.

[0004] 9,9-di-n-octylfluorene copolymer is a copolymer commonly used in light-emitting components. Palladium / phosphine ligand catalysis is often used to prepare 9,9-di-n-octylfluorene copolymer, but phosphine ligands are not only highly toxic, but also extremely sensitive to air and water vapor, making the conditions for catalytic reactions involving phosphine ligands extremely harsh. In order to solve the problem of high toxicity of phosphine ligands, the present invention provides a method for synthesizing 9,9-di-n-octylfluorene copolymer without using phosphine ligands, and explores the application of 9,9-di-n-octylfluorene copolymer in the preparation of hole transport layers of perovskite solar cells. Summary of the invention

[0005] In view of the deficiencies in the above-mentioned prior art, the present invention provides a method for synthesizing a 9,9-di-n-octylfluorene copolymer. The present invention adopts a nitrogen heterocyclic carbene palladium complex to catalyze the preparation of the 9,9-di-n-octylfluorene copolymer, which has the advantages of high catalytic efficiency and can obtain a high molecular weight and narrow distribution 9,9-di-n-octylfluorene copolymer, thereby overcoming the problems of high toxicity of phosphine ligand catalysts.

[0006] The object of the present invention is to provide a method for synthesizing a 9,9-di-n-octylfluorene copolymer, comprising the following steps:

[0007] Under the action of nitrogen heterocyclic carbene palladium complex and organic base, 9,9-dioctylfluorene-2,7-bis(boric acid pinacol ester) and 2,5-dichloropyridine react to obtain 9,9-dioctylfluorene copolymer;

[0008] The structure of the nitrogen heterocyclic carbene palladium complex is shown in formula (I):

[0009]

[0010] Formula (I)

[0011] Wherein, R1, R2 and R3 are independently selected from H or C1~C6 alkyl, and X is selected from Cl or Br.

[0012] In some embodiments of the present invention, R1, R2 and R3 are independently selected from H or C1~C3 alkyl.

[0013] In some embodiments of the present invention, R1 or R2 is independently selected from methyl, ethyl or isopropyl, R3 is selected from H or methyl, and R1 is the same as R2.

[0014] In some embodiments of the present invention, the molar ratio of the 2,5-dichloropyridine, 9,9-dioctylfluorene-2,7-bis(boric acid pinacol ester) and the nitrogen heterocyclic carbene palladium complex is 1:1:0.005-0.015.

[0015] In some embodiments of the present invention, the organic base is selected from potassium tert-butoxide.

[0016] In some embodiments of the present invention, the molar ratio of the organic base to 2,5-dichloropyridine is 3-5:1.

[0017] In some embodiments of the present invention, the reaction temperature is 60-100° C. and the reaction time is 8-16 hours.

[0018] In some embodiments of the present invention, the reaction further comprises a solvent, and the solvent is selected from a mixed solvent of tetrahydrofuran and water.

[0019] In some embodiments of the present invention, the volume ratio of tetrahydrofuran to water is 2-4:1.

[0020] In some embodiments of the present invention, after the reaction is completed, a purification step is further included.

[0021] In some embodiments of the present invention, another object of the present invention is to provide a method for synthesizing a 9,9-di-n-octylfluorene copolymer and use the 9,9-di-n-octylfluorene copolymer in preparing perovskite solar cells.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] (1) The present invention adopts nitrogen heterocyclic carbene palladium complex as catalyst to prepare 9,9-di-n-octylfluorene copolymer, which has the advantage of high catalytic efficiency and can obtain high molecular weight and narrow distribution 9,9-di-n-octylfluorene copolymer, thus overcoming the problem of high toxicity of phosphine ligand catalyst.

[0024] (2) The 9,9-di-n-octylfluorene copolymer prepared by the present invention is used to prepare the hole transport layer of the perovskite solar cell, which is beneficial to improving the efficiency of the perovskite solar cell. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is the H NMR spectrum of the 9,9-di-n-octylfluorene copolymer prepared in Example 6. DETAILED DESCRIPTION

[0026] In order to enable those skilled in the art to better understand the technical solutions of the present invention, the technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0027] All raw materials of the present invention are conventionally commercially available.

[0028] The PTAA used in Examples 7-9 and Comparative Examples 2-3 is derived from Example 2 of CN118978672A.

[0029] The structural formula of the 9,9-di-n-octylfluorene copolymer prepared in the examples and comparative examples of the present invention is as follows:

[0030] ;

[0031] The nitrogen heterocyclic carbene palladium complexes of each embodiment of the present invention are prepared by the following reaction route:

[0032] .

[0033] Example 1

[0034] This embodiment provides a nitrogen heterocyclic carbene palladium complex C1, and the preparation method thereof comprises the following steps:

[0035] S1. 2,4,6-trimethylaniline (4.4mmol), 4,7-di-tert-butylacenaphthenequinone (2mmol), and anhydrous zinc chloride (4.6mmol) were added to a 100 ml side-mouth bottle in sequence, and 50 ml of glacial acetic acid was added as solvent. The mixture was refluxed at 120°C under N2 protection for 5 hours. After the reaction was completed, the mixture was cooled to room temperature. An orange-yellow solid was generated in the solution. The mixture was filtered and the filter cake was rinsed with glacial acetic acid for several times to remove the unreacted raw materials. The solid obtained by filtration was dried and dissolved in dichloromethane. The solution was dezincified with 100 mL of potassium oxalate aqueous solution (4.6 g / L). After stirring for 5 hours, the white zinc salt was removed by filtration. The remaining organic layer was extracted with water for several times. After the solvent was removed by vacuum distillation, the solution was recrystallized with (dichloromethane / n-hexane) to obtain orange-yellow crystals, i.e., diimine compound D1, with a yield of 64%;

[0036] S2. Weigh the diimine compound D1 (1.0 mmol) into a 25 ml eggplant-shaped bottle, add 3-4 ml of chloromethyl ether to dissolve it, react at 100 ° C for 24 h under N2 protection, and recrystallize from dichloromethane / petroleum ether to obtain compound E1 with a yield of 78%;

[0037] Weigh compound E1 (0.2 mmol), palladium chloride (0.22 mmol), potassium carbonate (2 mmol), and 3-chloropyridine (1.2 mmol) into a reaction bottle, add 4 ml of acetone, and react at 60°C for 8 h. After the reaction is completed, extract with water to remove excess potassium carbonate, and recrystallize the organic layer with dichloromethane / n-hexane to obtain a yellow solid, namely, nitrogen heterocyclic carbene palladium complex C1, with a yield of 45%;

[0038] The NMR data of the nitrogen heterocyclic carbene palladium complex C1 are as follows:

[0039] 1 H NMR (600 MHz, CDCl3) δ 8.67 (d, J = 2.3 Hz, 1H), 8.59 (dd, J = 5.6,1.3 Hz, 1H), 7.69 (s, 2H), 7.58 (t, J = 8.3, 1.8 Hz, 1H), 7.15 (s, 4H), 7.12– 7.09 (m, 1H), 6.98 (d, J = 1.3 Hz, 2H), 2.45 (d, J = 13.5 Hz, 17H), 1.31 (s, 16H).

[0040] 13C NMR (101 MHz, CDCl3) δ 155.18, 151.42, 150.65, 149.73, 139.41,139.03, 137.63, 136.17, 133.81, 132.09, 129.54, 129.00, 126.38, 125.43,124.43, 122.99, 118.94, 35.53, 31.46, 21.53, 19.29.

[0041] Example 2

[0042] This embodiment provides a nitrogen heterocyclic carbene palladium complex C2, and the preparation method thereof comprises the following steps:

[0043] S1. 2,6-diethylaniline (4.4mmol), 4,7-di-tert-butylacenaphthenequinone (2mmol), and anhydrous zinc chloride (4.6mmol) were added to a 100 ml side-mouth bottle in sequence, and 50 ml of glacial acetic acid was added as solvent. The mixture was refluxed at 120°C under N2 protection for 5 hours. After the reaction was completed, the mixture was cooled to room temperature. An orange-yellow solid was generated in the solution. The solution was filtered and the filter cake was rinsed with glacial acetic acid for several times to remove the unreacted raw materials. The solid obtained by filtration was dried and dissolved in dichloromethane. The solution was dezincified with 100 mL of potassium oxalate aqueous solution (4.6 g / L). After stirring for 5 hours, the white zinc salt was removed by filtration. The remaining organic layer was extracted with water for several times. After the solvent was removed by vacuum distillation, the solution was recrystallized with (dichloromethane / n-hexane) to obtain orange-yellow crystals, i.e., diimide compound D2, with a yield of 62%;

[0044] S2. Weigh the diimine compound D2 (1.0 mmol) into a 25 ml eggplant-shaped bottle, add 3-4 ml of chloromethyl ether to dissolve it, react at 100 ° C for 24 h under N2 protection, and recrystallize from dichloromethane / petroleum ether to obtain compound E2 with a yield of 52%;

[0045] Weigh compound E2 (0.2 mmol), palladium chloride (0.22 mmol), potassium carbonate (2 mmol), and 3-chloropyridine (1.2 mmol) into a reaction bottle, add 4 ml of acetone, and react at 60°C for 8 h. After the reaction, extract with water to remove excess potassium carbonate, and recrystallize the organic layer with dichloromethane / n-hexane to obtain a yellow solid, i.e., nitrogen heterocyclic carbene palladium complex C2, with a yield of 56%;

[0046] The NMR data of the nitrogen heterocyclic carbene palladium complex C2 are as follows:

[0047] 1H NMR (400 MHz, CDCl3) δ 8.58 (d, J = 2.3 Hz, 1H), 8.49 (dd, J = 5.5,1.1 Hz, 1H), 7.68 (d, J = 0.9 Hz, 2H), 7.62 – 7.54 (m, 3H), 7.43 (d, J = 7.7Hz, 4H), 7.08 (dd, J = 8.2, 5.5 Hz, 1H), 6.98 (d, J = 1.0 Hz, 2H), 2.98 (t, J= 15.3, 7.7 Hz, 4H), 2.80 (t, J = 15.4, 7.5 Hz, 4H), 1.28 (s, 18H), 1.11 (t,J = 7.5 Hz, 12H).

[0048] 13 C NMR (101 MHz, CDCl3) δ 156.37, 151.35, 150.57, 149.66, 142.32,139.67, 137.59, 134.98, 132.07, 130.37, 129.02, 126.69, 126.44, 125.43,124.43, 122.93, 119.60, 35.53, 31.35, 25.11, 14.69.

[0049] Example 3

[0050] This embodiment provides a nitrogen heterocyclic carbene palladium complex C3, and its preparation method comprises the following steps:

[0051] S1. 2,6-diisopropylaniline (4.4mmol), 4,7-di-tert-butylacenaphthenequinone (2mmol), and anhydrous zinc chloride (4.6mmol) were added to a 100 ml side-mouth bottle in sequence, and 50 ml of glacial acetic acid was added as solvent. The reaction was refluxed at 120°C under N2 protection for 5 hours. After the reaction was completed, the solution was cooled to room temperature. An orange-yellow solid was generated in the solution. The solution was filtered and the filter cake was rinsed with glacial acetic acid for several times to remove the unreacted raw materials. The solid obtained by filtration was dried and dissolved in dichloromethane. The solution was dezincified with 100 mL of potassium oxalate aqueous solution (4.6 g / L). After stirring for 5 hours, the white zinc salt was removed by filtration. The remaining organic layer was extracted with water for several times. After the solvent was removed by vacuum distillation, the solution was recrystallized with (dichloromethane / n-hexane) to obtain orange-yellow crystals, i.e., diimine compound D3, with a yield of 68%;

[0052] S2. Weigh the diimine compound D3 (1.0 mmol) into a 25 ml eggplant-shaped bottle, add 3-4 ml of chloromethyl ether to dissolve it, exhaust the air in the bottle with N2 and seal it, react at 100 ° C for 24 hours, and after treatment, obtain compound E3 with a yield of 48%;

[0053] Weigh compound E3 (0.2 mmol), palladium chloride (0.22 mmol), potassium carbonate (2 mmol), and 3-chloropyridine (1.2 mmol) into a reaction bottle, add 4 ml of acetone, and react at 60°C for 8 h. After the reaction, extract with water to remove excess potassium carbonate, and recrystallize the organic layer with dichloromethane / n-hexane to obtain a yellow solid, i.e., nitrogen heterocyclic carbene palladium complex C3, with a yield of 57%;

[0054] The NMR data of the nitrogen heterocyclic carbene palladium complex C3 are as follows:

[0055] 1 H NMR (400 MHz, CDCl3) δ 8.70 (d, J = 2.3 Hz, 1H), 8.62 (dd, J = 5.5,1.1 Hz, 1H), 7.64 (d, J = 12.3 Hz, 4H), 7.57 (d, J = 8.3 Hz, 1H), 7.49 (d, J= 7.8 Hz, 4H), 7.10 (dd, J = 8.2, 5.6 Hz, 1H), 6.81 (s, 2H), 3.39 (t, J =13.4, 6.7 Hz, 4H), 1.46 (d, J = 6.6 Hz, 12H), 1.24 (s, 18H), 0.91 (d, J = 6.8Hz, 12H).

[0056] 13 C NMR (101 MHz, CDCl3) δ 157.96, 150.81, 149.74, 147.42, 140.81,137.55, 133.99, 132.00, 130.82, 128.92, 126.41, 125.68, 124.79, 124.44,122.66, 120.90, 35.45, 31.18, 29.01, 25.83, 24.39.

[0057] Example 4

[0058] This embodiment provides a 9,9-di-n-octylfluorene copolymer, and the preparation method thereof comprises the following steps:

[0059] Under nitrogen protection, 2,5-dichloropyridine (1.0 mmol), 9,9-dioctylfluorene-2,7-bis(boric acid pinacol ester) (1.0 mmol), potassium tert-butoxide (4.0 mmol), nitrogen heterocyclic carbene palladium complex C1 (0.01 mmol) and 10 mL of tetrahydrofuran / water (3:1) as solvent were added to a crimped round-bottom microwave reaction tube, and the mixture was stirred at 80°C for 12 hours. After the reaction was completed, it was cooled to room temperature, and the polymer was precipitated with methanol, washed several times, dried, and weighed to obtain 9,9-di-n-octylfluorene copolymer with a yield of 62%. The 9,9-di-n-octylfluorene copolymer was characterized by GPC, and the number average molecular weight Mn of the 9,9-di-n-octylfluorene copolymer was 21.5 kDa, and the molecular weight distribution PDI was 1.6.

[0060] Example 5

[0061] This embodiment provides a 9,9-di-n-octylfluorene copolymer, and the preparation method thereof comprises the following steps:

[0062] Under nitrogen protection, 2,5-dichloropyridine (1.0 mmol), 9,9-dioctylfluorene-2,7-bis(boric acid pinacol ester) (1.0 mmol), potassium tert-butoxide (4.0 mmol), nitrogen heterocyclic carbene palladium complex C2 (0.01 mmol) and 10 mL of tetrahydrofuran / water (3:1) as solvent were added to a crimped round-bottom microwave reaction tube, and the mixture was stirred at 80°C for 12 hours. After the reaction was completed, it was cooled to room temperature, and the polymer was precipitated with methanol, washed several times, dried, and weighed to obtain 9,9-dioctylfluorene copolymer with a yield of 67%. GPC characterization of 9,9-dioctylfluorene copolymer showed that the number average molecular weight Mn of 9,9-dioctylfluorene copolymer was 27.3 kDa, and the molecular weight distribution PDI was 2.5.

[0063] Example 6

[0064] This embodiment provides a 9,9-di-n-octylfluorene copolymer, and the preparation method thereof comprises the following steps:

[0065] Under nitrogen protection, 2,5-dichloropyridine (1.0 mmol), 9,9-dioctylfluorene-2,7-bis(boric acid pinacol ester) (1.0 mmol), potassium tert-butoxide (4.0 mmol), nitrogen heterocyclic carbene palladium complex C3 (0.01 mmol) and 10 mL of tetrahydrofuran / water (3:1) as solvent were added to a crimped round-bottom microwave reaction tube, and the mixture was stirred at 80°C for 12 hours. After the reaction was completed, it was cooled to room temperature, and the polymer was precipitated with methanol, washed several times, dried, and weighed to obtain 9,9-di-n-octylfluorene copolymer with a yield of 73%. The 9,9-di-n-octylfluorene copolymer was characterized by nuclear magnetic resonance and GPC. The number average molecular weight Mn of the 9,9-di-n-octylfluorene copolymer was 24.6 kDa, and the molecular weight distribution PDI was 2.3.

[0066] Comparative Example 1

[0067] This embodiment provides a 9,9-di-n-octylfluorene copolymer, and the preparation method thereof comprises the following steps:

[0068] The difference from Example 3 is that the nitrogen heterocyclic carbene palladium complex is replaced by Pd(PPh3)4, and the remaining steps are the same as Example 3, and 9,9-di-n-octylfluorene copolymer is obtained with a yield of 53%; the 9,9-di-n-octylfluorene copolymer is characterized by GPC, and the number average molecular weight Mn of the 9,9-di-n-octylfluorene copolymer is 10.5 kDa, and the molecular weight distribution PDI is 2.1.

[0069] Example 7

[0070] This embodiment provides a pin-type perovskite solar cell, wherein the specific cell structure is ITO / 9,9-di-n-octylfluorene copolymer: PTAA / perovskite active layer / PCBM / BCP / Ag, and the preparation method thereof comprises the following steps:

[0071] (1) Cleaning of the transparent substrate layer: First, take out the ITO transparent conductive glass, tear off the plastic protective film on the surface, and first use detergent to gently wipe the surface oil and dirt, and then ultrasonically clean it in a 0.2wt% detergent aqueous solution, deionized water, and isopropanol for 15 minutes respectively. Finally, use nitrogen to blow dry the isopropanol on the ITO surface and put it in a box for later use.

[0072] (2) Deposition of hole transport layer: PTAA and the 9,9-di-n-octylfluorene copolymer prepared in Example 4 were prepared into a 2.5 mg / mL precursor solution, the mass ratio of PTAA and the 9,9-di-n-octylfluorene copolymer prepared in Example 4 was 1:1, the solvent was chlorobenzene, the cleaned ITO was first placed in an ultraviolet ozone cleaning apparatus for surface hydrophilic treatment, and then the precursor solution was sucked out with a pipette and evenly covered on the ITO surface, and then coated on the surface by a scraper coating process.

[0073] (3) Preparation of wetting layer: The purchased aluminum oxide nanoparticle (<50 nm) dispersion (20%) was mixed with isopropanol at a volume ratio of 1:50 (aluminum oxide dispersion: isopropanol) to prepare an aluminum oxide precursor solution. The prepared aluminum oxide precursor solution was then aspirated with a pipette and evenly covered on the surface of the hole transport layer. The solvent was dried by spin coating (100 rpm / min, 3 s; 5000 rpm / min, 20 s).

[0074] (4) Preparation of perovskite active layer: The FAPbI3 system perovskite precursor solution (1000 rpm / min, 3s; 5000 rpm / min, 30s, 100 μL chlorobenzene was added as anti-solvent at 21s) was aspirated with a pipette and evenly covered on the surface of the wetting layer to form a perovskite active layer, and then annealed on a hot stage at 100°C for 30-60 min.

[0075] (5) Deposition of electron transport layer: Weigh 20 mg of PCBM and add 1 mL of chlorobenzene to prepare the precursor solution of the electron transport layer. The electron transport layer precursor solution was deposited on the surface of the perovskite active layer by spin coating (500 rpm / min, 3 s; 2500 rpm / min, 20 s).

[0076] (6) Deposition of hole blocking layer: 8 mg of BCP was weighed and 16 mL of isopropanol was added to prepare a precursor solution. The prepared precursor solution was then aspirated with a pipette and evenly covered on the surface of the hole blocking layer. The solvent was dried by spin coating (100 rpm / min, 3 s; 5000 rpm / min, 20 s).

[0077] (7) Deposition of metal electrode layer: A 100 nm thick Ag film was thermally evaporated under high vacuum at an evaporation rate of 0.3 Å / s for 20 nm and then deposited on the surface of the hole blocking layer at 1 Å / s to a thickness of 100 nm.

[0078] Example 8

[0079] This embodiment provides a pin-type perovskite solar cell, which differs from Embodiment 7 only in that: in point (2) of Embodiment 7, "the 9,9-di-n-octylfluorene copolymer prepared in Embodiment 4" is replaced by "the 9,9-di-n-octylfluorene copolymer prepared in Embodiment 5", and the remaining steps are the same as Embodiment 7.

[0080] Example 9

[0081] This embodiment provides a pin-type perovskite solar cell, which differs from Embodiment 7 only in that: in point (2) of Embodiment 7, "the 9,9-di-n-octylfluorene copolymer prepared in Embodiment 4" is replaced by "the 9,9-di-n-octylfluorene copolymer prepared in Embodiment 6", and the remaining steps are the same as Embodiment 7.

[0082] Comparative Example 2

[0083] This comparative example provides a pin-type perovskite solar cell, which differs from Example 7 only in that: in point (2) of Example 7, "the 9,9-di-n-octylfluorene copolymer prepared in Example 4" is replaced by "the 9,9-di-n-octylfluorene copolymer prepared in Comparative Example 1", and the remaining steps are the same as Example 7.

[0084] Comparative Example 3

[0085] This comparative example provides a pin-type perovskite solar cell, which differs from Example 7 only in that: the sentence "PTAA and the 9,9-di-n-octylfluorene copolymer prepared in Example 4 are configured into a 2.5 mg / mL precursor solution, and the mass ratio of PTAA and the 9,9-di-n-octylfluorene copolymer prepared in Example 4 is 1:1" in point (2) of Example 7 is replaced by "PTAA is configured into a 2.5 mg / mL precursor solution", and the remaining steps are the same as Example 7.

[0086] The performance of the pin-type perovskite solar cells of Examples 7 to 9 and Comparative Examples 2 to 3 was tested. The test method is as follows. The results are shown in Table 1.

[0087] The JV characteristic curve of the device was measured using a Keithley 2440 light source under a simulated AM1.5G spectrum.

[0088] The light intensity was calibrated using a solar simulator (Newport, 91160) from NREL using a standard silicon solar cell device. The effective measurement area was 0.07 cm 2 , under reverse and forward bias scans, the scan rate was 100mV / s and the bias range was from -0.2V to 1.2V.

[0089] Table 1. Performance of perovskite solar cells of Examples 7-9 and Comparative Examples 2-3.

[0090] sample Voc(V) <![CDATA[Jsc(mA / cm 2 )]]> FF(%) PCE(%) Example 7 1.10 19.75 78.62 17.08 Example 8 1.08 24.44 73.96 19.52 Example 9 1.12 22.06 75.35 18.62 Comparative Example 2 0.86 14.91 66.41 8.52 Comparative Example 3 0.95 19.37 75.38 13.87

[0091] As can be seen from Table 1, the 9,9-di-n-octylfluorene copolymer prepared in Examples 7 to 9 of the present invention is mixed with PTAA to prepare a hole transport layer, which is beneficial to improving the efficiency of the perovskite solar cell.

[0092] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that after reading the specification of this application, the technicians can still modify or replace the specific implementation mode of the present invention with equivalents, but these modifications or changes do not deviate from the scope of protection of the pending claims of the present application.

Claims

1. A method for synthesizing a 9,9-di-n-octylfluorene copolymer, characterized in that: The steps include: Under the action of nitrogen heterocyclic carbene palladium complex and organic base, 9,9-dioctylfluorene-2,7-bis(boric acid pinacol ester) and 2,5-dichloropyridine react to obtain 9,9-dioctylfluorene copolymer; The structure of the nitrogen heterocyclic carbene palladium complex is shown in formula (I): Formula (I) Wherein, R1, R2 and R3 are independently selected from H or C1~C6 alkyl, and X is selected from Cl or Br.

2. The method for synthesizing the 9,9-di-n-octylfluorene copolymer according to claim 1, characterized in that: The R1, R2 and R3 are independently selected from H or C1~C3 alkyl.

3. The method for synthesizing the 9,9-di-n-octylfluorene copolymer according to claim 1, characterized in that: The R1 or R2 is independently selected from methyl, ethyl or isopropyl, R3 is selected from H or methyl, and R1 is the same as R2.

4. The method for synthesizing the 9,9-di-n-octylfluorene copolymer according to claim 1, characterized in that: The molar ratio of the 2,5-dichloropyridine, 9,9-dioctylfluorene-2,7-bis(boric acid pinacol ester) and the nitrogen heterocyclic carbene palladium complex is 1:1:0.005-0.

015.

5. The method for synthesizing the 9,9-di-n-octylfluorene copolymer according to claim 4, characterized in that: The organic base is selected from potassium tert-butoxide.

6. The method for synthesizing the 9,9-di-n-octylfluorene copolymer according to claim 5, characterized in that: The molar ratio of the organic base to 2,5-dichloropyridine is 3-5:

1.

7. The method for synthesizing the 9,9-di-n-octylfluorene copolymer according to claim 1, characterized in that: The reaction temperature is 60-100° C. and the reaction time is 8-16 hours.

8. The method for synthesizing the 9,9-di-n-octylfluorene copolymer according to claim 1, characterized in that: The reaction further comprises a solvent, and the solvent is selected from a mixed solvent of tetrahydrofuran and water.

9. The method for synthesizing the 9,9-di-n-octylfluorene copolymer according to claim 8, characterized in that: The volume ratio of tetrahydrofuran to water is 2-4:

1.

10. The method for synthesizing the 9,9-di-n-octylfluorene copolymer according to claim 1, characterized in that: After the reaction is completed, a purification step is also included.

Citation Information

Cited By

  • Synthesis and application of organic semiconductor electron transport layer material

    CN120059138A

  • Synthesis of organic semiconductor electron transport layer material and application thereof

    CN120059138B